2021
DOI: 10.1093/mnras/stab3312
|View full text |Cite
|
Sign up to set email alerts
|

The dust-continuum size of TNG50 galaxies at z = 1–5: a comparison with the distribution of stellar light, stars, dust, and H2

Abstract: We present predictions for the extent of the dust-continuum emission of main-sequence galaxies drawn from the TNG50 simulation between z = 1–5. We couple the radiative transfer code SKIRT to the output of the TNG50 simulation and measure the dust-continuum half-light radius of the modeled galaxies, assuming a Milky Way dust type and a metallicity dependent dust-to-metal ratio. The dust-continuum half-light radius at observed-frame 850 μm is up to ∼75 per cent larger than the stellar half-mass radius, but signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 96 publications
8
48
1
Order By: Relevance
“…As discussed in Sect. 5, this apparent discrepancy between optical and FIR sizes of MS galaxies does not, however, necessarily translate into stellar half-mass radius discrepancy, as complex obscuration biases need to be accounted for when converting half-light stellar radius into halfmass stellar radius (e.g., Lang et al 2019;Suess et al 2019;Popping et al 2022). For example, the FIR sizes inferred in our study agree quantitatively with the mean redshift-independent half-mass stellar radius of SFGs measured by Suess et al (2019).…”
Section: The Fir Sizes Of Ms Galaxiessupporting
confidence: 61%
See 4 more Smart Citations
“…As discussed in Sect. 5, this apparent discrepancy between optical and FIR sizes of MS galaxies does not, however, necessarily translate into stellar half-mass radius discrepancy, as complex obscuration biases need to be accounted for when converting half-light stellar radius into halfmass stellar radius (e.g., Lang et al 2019;Suess et al 2019;Popping et al 2022). For example, the FIR sizes inferred in our study agree quantitatively with the mean redshift-independent half-mass stellar radius of SFGs measured by Suess et al (2019).…”
Section: The Fir Sizes Of Ms Galaxiessupporting
confidence: 61%
“…Using high-resolution ALMA and Hubble Space Telescope observations of 20 submillimeter-selected galaxies, Lang et al (2019) argues instead that the discrepancy between FIR and optical sizes is mostly due to observational biases in which important radial color gradients yield very discrepant half-light and half-mass radii. This observational finding has recently been supported by TNG50 simulations coupled with state-of-the-art radiative transfer code to study the FIR, optical, and half-mass radius of thousands high-redshift 10 9 − 10 11 M MS galaxies (Popping et al 2022). Indeed, in these simulations it is found that while the FIR half-light radius correlates with the radius containing half the star formation in galaxies, strong and un-corrected obscuration of the stellar light toward the galaxy centre increases significantly the apparent extent of the disk sizes in the optical.…”
Section: Compact Star Forming Extent ?mentioning
confidence: 66%
See 3 more Smart Citations